ANALISIS DETERMINAN INDEKS KUALITAS LINGKUNGAN HIDUP 34 PROVINSI DI INDONESIA TAHUN 2020-2022 MENGGUNAKAN PENDEKATAN EKONOMI - Aris Setya Novanto; Zulfa Emalia (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2025)
One of the key challenges in economic development lies in balancing economic growth with environmental sustainability. This study investigates the determinants of the Environmental Quality Index (EQI) across 34 provinces in Indonesia from 2020 to 2022 using an economic perspective. The EQI serves as a composite indicator reflecting environmental conditions based on three primary dimensions: air quality, water quality, and land cover. The independent variables in this analysis include the contribution of the Gross Regional Domestic Product (GRDP) from the agricultural and mining sectors, poverty levels, and the total area of forest cover. The study employs panel data regression using a Fixed Effect Model (FEM) approach. The findings reveal that the GRDP of the agricultural sector has a negative and significant influence on EQI, suggesting that unsustainable agricultural practices can degrade environmental quality. Similarly, the mining sector’s contribution exhibits a significantly negative relationship with EQI, underscoring the adverse environmental effects of resource extraction. Moreover, high poverty rates are associated with lower EQI values, indicating that limited infrastructure and low environmental awareness may hinder environmental preservation. In contrast, forest area demonstrates a positive and significant effect on EQI, emphasizing the vital role of natural ecosystems in supporting environmental health and sustainability.